The Effect of the Kinetic Collections According to the Outcome of Movement Performance in Learning Some Skills in Basketball for Young Players - Zainab Abdul Sadah Ali Marhoon; Ayman Hani Abdul-Jabburi; Mustafa Adil Alwan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The Study Aimed to: The numbers of movement collection according to information about the result.Knowing the effect of movement collection on the basis of information about the result in learning someskills for basketball for young players. The design of the two equivalents groups was used, as the researchcommunity is determined the players of Al Mahaweel Club in basketball for the youth category for the sportsseason (2018-2019) by (20) players, that the research community is divided into two equal groups (control,experimental) then items foe collection of movement is designed, so the total educational units reached (8)units, in light of the results that the current research reached:1. The trainer’s approach has a positive effect in learning some basketball skills.2. The group which used the kinetic collections was better than the other group in learning some skills inbasketball.In light of the results of the research and its conclusions, the current research has reached:1. Adopting the kinetic collections to learn the basic skills of basketball as being successful and effective.2. Work to take advantage of the results of the study to improve the level of skill performance in basketballfor other groups.